Melatih Kreativitas Anak Usia Dini Melalui Media Pembelajaran Finger Painting - Hendrawati, Irena Ketrin; Syofiyanti, Dessy (PeDaPAUD: Jurnal Pendidikan Dasar dan PAUD, 2025)
This study aims to determine the implementation of finger painting activities in learning at PAUD Pertiwi and analyze its influence on early childhood creativity. Using a descriptive qualitative approach, this study focuses on direct observation of the learning process without intervention from researchers. Data were collected through observation, in-depth interviews, and documentation, to describe the involvement of teachers and children in finger painting activities. The results of the study indicate that finger painting is not only a medium for visual expression, but is also able to stimulate children's imagination, color exploration, and fine motor coordination. This activity provides space for children to be free to create without pressure, thus supporting the development of creativity naturally. Consistent implementation and support from teachers play an important role in optimizing the benefits of this activity. These findings are expected to be a reference for PAUD educators in designing fun and creative learning through art activities that are appropriate to the child's developmental stage.